2022
DOI: 10.3390/f13111834
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tree Species on Moso Bamboo (Phyllostachys edulis (Carriere) J. Houzeau) Fine Root Morphology, Biomass, and Soil Properties in Bamboo–Broadleaf Mixed Forests

Abstract: Understanding fine root characteristics in relation to soil properties of bamboo–broadleaf mixed forests may help optimize belowground production management and ecological functions in mixed-forest ecosystems. In this study, we compared four different bamboo–broadleaf mixed forests: Castanopsis chinensis (Sprengel) Hance with moso bamboo (CCB), Alniphyllum fortunei (Hemsl.) Makino with moso bamboo (AFB), Choerospondias axillaris (Roxb.) Burtt and Hill with moso bamboo (CAB), and Castanopsis fargesii Franch wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…And the fine root morphology all showed strong correlation with soil nutrients. It is suggested that the morpho-plasticity is largely affected by soil nutrient heterogeneity, which is the same as the related research results of many scholars [4,9,70,71]. This study thus clarifies that for subtropical woody plants, soil AP is the main factor driving root trait variation.…”
Section: Relationship Between Morphological Characteristics Of Fine R...supporting
confidence: 83%
See 3 more Smart Citations
“…And the fine root morphology all showed strong correlation with soil nutrients. It is suggested that the morpho-plasticity is largely affected by soil nutrient heterogeneity, which is the same as the related research results of many scholars [4,9,70,71]. This study thus clarifies that for subtropical woody plants, soil AP is the main factor driving root trait variation.…”
Section: Relationship Between Morphological Characteristics Of Fine R...supporting
confidence: 83%
“…In this study, it was found that FRB, RLD and RAD under different fertilization treatments showed a decreasing pattern with the increase in soil depth, and the fine root biomass of Sapindus mukorossi was significantly reduced by 25.39%-63.01% in the soil layer of 20-40 cm, compared to 0-20 cm. It indicates that the fine roots of Sapindus mukorossi were mainly distributed in the top soil layer and, similarly, other tree species such as poplar (Populus), moso bamboo (Phyllostachys edulis) and pomelo (Citrus maxima) have similar results [4,14,32]. The topsoil layer is the main provider of nutrients for plant roots [10].…”
Section: Effect Of Fertilization On Fine Root Traitsmentioning
confidence: 83%
See 2 more Smart Citations
“…For example, research indicated that when the intercropping ratio of moso bamboo and broadleaved trees was in the range of 20-30%, optimal soil nutrients were achieved, leading to the best growth performance of moso bamboo (Zhang et al, 2020a). Similarly, The intercropping of Q. tumidinoda with other tree species had a certain impact on the growth of the bamboo forest, and the extent of this impact depended on the choice of tree species (Zhou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%